O proučevanju in razumevanju turških alevijskih skupnosti - Bjelica, Maja (Glasnik Slovenskega etnološkega društva, 2020)
The article offers an insight into the characteristics of the Turkish Alevi communities. These communities are defined by researchers as syncretistic branches of Shi'a Islam, with roots in Central Asian shamanism. The author focuses on a critical insight into the literature that treats these communities in the contexts of western traditions of religious studies, which are too narrow for understanding Aleviness, since they follow the principles of homogenization and codification - these principles do not seem to be compatible with the Alevi practice dynamics. The author emphasises the crucial role of ethnographic research that allows for a deeper understanding of such fluid and heterogeneous religious communities.
Keywords: Alevi studies; alevijske študije; alevijstvo; Aleviness; anthropology; antropologija; islam; religije; religijski sinkretizem; religions; religious syncretism; Turkish Alevis; turški aleviji